2008
DOI: 10.1111/j.1095-8649.2008.01842.x
|View full text |Cite
|
Sign up to set email alerts
|

The strontium content of roe collected from spawning brown troutSalmo truttaL. reflects recent otolith microchemistry

Abstract: The relationship between the strontium content of the outer layers of otoliths (an indication of recent marine, estuarine or riverine habitat use) and the strontium content of roe in ripe female brown trout Salmo trutta was examined in fish collected from the Pomahaka River and the lower reaches of the Clutha River, South Island, New Zealand. A close relationship was found between the strontium content of roe and the outer layers of otoliths. This finding suggests that spawned eggs collected from redds could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
4
13
1
Order By: Relevance
“…The study builds on previous work by Kalish (1990) who identified differing Sr levels in anadromous and freshwater rainbow trout, Waite et al (2008) who confirmed that Sr levels in eggs reflect the recent maternal habitat use and Gabrielsson et al This is the first study to utilise this approach to precisely map the upstream extent of spawning by anadromous fish.…”
Section: Evaluation Of Methodsmentioning
confidence: 54%
See 3 more Smart Citations
“…The study builds on previous work by Kalish (1990) who identified differing Sr levels in anadromous and freshwater rainbow trout, Waite et al (2008) who confirmed that Sr levels in eggs reflect the recent maternal habitat use and Gabrielsson et al This is the first study to utilise this approach to precisely map the upstream extent of spawning by anadromous fish.…”
Section: Evaluation Of Methodsmentioning
confidence: 54%
“…High concentrations of Sr in eggs indicate that the female fish have been living in a Sr-rich environment during the period of egg formation (Kalish 1990;Waite et al 2008). The proportion of egg samples with relatively high-Sr concentrations (>150 nmole SrAEg )1 dry weight egg) was high in the two tributaries located below the Taieri River Gorge, but consistently <150 nmole SrAEg )1 egg in the tributaries located above the gorge.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…a transect ran in a cross-section from one otolith edge (starting at 0.30 or 0.48 mm, depending on the otolith) through the primordia (otolith centre) and to the opposite edge (c. 3.0 mm). Sr and Ca levels were measured across the otolith sections with Photon induced Xray Emission analysis using a proton microprobe on a 3 megavolt Van de Graaf accelerator (Waite et al 2008). Simple linear regressions were applied to ascertain the significance of the regression correlation coefficients between MeHg and δ 13 C and δ 15 N in trout muscle tissues .…”
Section: Methodsmentioning
confidence: 99%